Alumina nanoparticle stabilized nanoemulsion systems: Characterization, physicochemical evaluation and optimization for efficient hydrocarbon recovery - Akash T.; Verma V.; Pal N. (My University, 2025)
The paper investigates the viability of alumina nanoparticles dispersed into sodium dodecyl sulfate (anionic) surfactant-stabilized nanoemulsions in enhanced oil recovery (EOR). The size distribution data (of nanoemulsion droplets) was modelled by Gaussian, Galton and Cauchy-Lorentz distribution models, with the system's heterogeneity was most accurately described by the Galton (log-normal) model. Over a fifteen (15) day period, zeta potential measurements indicated a decrease from −65 to −70 mV to around −30 mV, suggesting a reduction in electrostatic repulsion between droplets and implying a stabilization process favorable for controlled coalescence. Interfacial studies revealed a significant decrease in oil-aqueous interfacial tension (IFT), attributed to the adsorption of alumina nanoparticles at the oil–water interface. The stability of the nanoemulsions was improved by the formation of a robust nanoparticle-laden interfacial film, which helped in displacing trapped oil effectively. Rheological investigations demonstrated a shear-thinning profile with enhanced viscoelasticity and the formation of a gel-like network, contributing to improved sweep efficiency in porous media. Overall, the combination of rheological data, interfacial studies, and droplet size distribution modelling indicates that alumina nanoemulsions possess favorable physicochemical properties. In summary, {anionic sodium dodecyl sulfate surfactant + alumina nanoparticle}-stabilized nanoemulsions represent a promising strategy for EOR applications in challenging reservoir conditions. © 2024 The Korean Society of Industrial and Engineering Chemistry